The Role of Fintech Technology in Improving Financial Inclusion and Financial System Stability - Imaningati, Sri; Mayndarto, Eko Cahyo; Huda, Miftakhul; Bakri, Asri Ady (PT. Anagata Sembagi Education, 2024)
The development of financial technology (fintech) has had a significant impact on improving financial inclusion and the stability of the global financial system. This study aims to explore the role of fintech technology in promoting people's access to financial services and its contribution to financial system stability. Fintech enables the creation of digital platforms that facilitate services such as electronic payments, peer-to-peer lending, and micro-investments, reaching segments previously neglected by the traditional banking sector. On the other hand, fintech innovations also strengthen supervision and transparency in financial transactions, potentially reducing the risk of financial instability. However, these developments also present challenges, including the need for appropriate regulation to address potential risks such as fraud and personal data management. This research uses a qualitative approach with literature analysis and case studies in several countries that have widely implemented fintech. The results show that fintech has great potential in increasing financial inclusion, but its sustainability and contribution to financial system stability depend on effective regulation and collaboration between the public and private sectors. This research lies in the lack of a thorough study of the regulatory challenges faced by developing countries in implementing fintech to increase financial inclusion without posing a risk of instability. A growing phenomenon is the rapid adoption of fintech in developing countries, yet its impact on financial system stability and associated risks are still not fully understood and adequately addressed